2015
DOI: 10.1038/jes.2015.34
|View full text |Cite
|
Sign up to set email alerts
|

Biomonitoring and evaluation of permethrin uptake in forestry workers using permethrin-treated tick-proof pants

Abstract: We conducted a randomized case-control trial to analyze uptake of the insecticide/arcaricide permethrin in wearers of permethrin-impregnated and non-impregnated pants in German forestry. Eighty-two male workers were each equipped for a 16-week period with permethrin-treated (test group) or with non-treated work pants (control group). Pants with or without lining to protect against cuts, obtained from two different distributors, were worn in each group. Urinary permethrin metabolite levels were measured by GC-M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Of note, permethrin metabolites were still present 4 weeks after the study concluded (Table 2). Rossbach, Kegel, Süß, and Letzel (2016) showed similar findings of increased permethrin uptake from permethrin-impregnated work pants in forestry workers, with highest levels of permethrin urinary metabolites found 1 week into the 16-week study period. It was suggested that washing the pants throughout the study may have resulted in decreased permethrin concentrated within the pants, resulting in decreased percutaneous penetration.…”
Section: Liquidssupporting
confidence: 72%
“…Of note, permethrin metabolites were still present 4 weeks after the study concluded (Table 2). Rossbach, Kegel, Süß, and Letzel (2016) showed similar findings of increased permethrin uptake from permethrin-impregnated work pants in forestry workers, with highest levels of permethrin urinary metabolites found 1 week into the 16-week study period. It was suggested that washing the pants throughout the study may have resulted in decreased permethrin concentrated within the pants, resulting in decreased percutaneous penetration.…”
Section: Liquidssupporting
confidence: 72%
“…Strong nonequilibrium uptake has been observed for polybrominated diphenylethers to cotton and polyester, nicotine and ethylpyridine on cotton and nylon, and chlorpyrifos on plush toys . Body uptake has been observed due to wearing clothing that has been treated with pesticides and flame retardants …”
Section: Introductionmentioning
confidence: 99%
“…Biomonitoring studies have shown that individuals wearing permethrin-treated clothing have significantly higher concentrations of urinary permethrin metabolites than those wearing untreated or conventional clothing, suggesting dermal exposure to the active ingredient as a result of wearing treated clothing. [12][13][14] Among German and U.S. Army soldiers, the duration of wear was associated with permethrin biomarkers measured in urine. 8,12,14,15 In addition to the length of wear time, environmental temperature, physical workload, and perspiration have been associated with increased permethrin absorption in forestry workers and U.S. Army soldiers wearing permethrin-treated clothing and uniforms, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[12][13][14] Among German and U.S. Army soldiers, the duration of wear was associated with permethrin biomarkers measured in urine. 8,12,14,15 In addition to the length of wear time, environmental temperature, physical workload, and perspiration have been associated with increased permethrin absorption in forestry workers and U.S. Army soldiers wearing permethrin-treated clothing and uniforms, respectively. [16][17][18] These results correspond to a body of literature that indicates absorption of chemicals following dermal exposure is affected by environmental conditions.…”
Section: Introductionmentioning
confidence: 99%